Integration Of Science In Islamic Educational Institutions - Ainatul Mardhiyah (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2024)
The dichotomy of science is not new in the midst of the Indonesian people and nation, this issue has become a dialectic that continues to touch and adorn various studies and dialectics of intellectuals. Entities who consider religious knowledge and general knowledge as water and oil that cannot be combined, while other entities claim that knowledge is actually one because it is derived from one substance, it is Allah SWT from whom everything comes and from it everything will return.